A DMM-EMM-RSM hybrid technique on two-dimensional frequency-domain hydroelasticity of floating structures over variable bathymetry. (1st April 2020) - Liu, Xiaolei; Wang, Xuefeng; Xu, Shengwen
Abstract: This paper proposes a hybrid technique combining the discrete modules method (DMM) (Lu et al., 2016), the eigenfunction matching method (EMM) (Tsai et al., 2011) and a further extended Rankine source method (RSM) to treat the two-dimensional hydroelastic problem of floating structures over variable bathymetry. In the hybrid technique, DMM is employed to discrete a floating structure into a set of rigid modules connected by elastic beams with equivalent deformation conditions of the structure; the incident wave potential over variable bathymetry without the presence of floating structures is obtained by EMM; a Rankine source method developed by Feng et al. (2017) is further extended to gain the diffracted and radiated wave potentials with the discreted multi-rigid-modules over variable bathymetry. A coupled model for the hydroelasticity of floating structures over variable bathymetry can be established by substituting the external wave loads exerted by the obtained incident, diffracted and radiated potentials into the multi-rigid-body dynamic equation by DMM in the frequency-domain. The convergence of the hybrid technique is validated through a good agreement against published data (Riyansyah et al., 2010) for hydroelastic responses of a two-dimensional floating structure over a flat seabed. Effects of sloping seabeds on hydroelastic responses of the floating structure are preliminarily investigated by the present hybrid technique. Highlights: The proposed hybrid technique combines the DMM, the EMM and a further extended RSM. The convergence of the method is validated by a good agreement against published data. Effects of sloping seabeds on hydroelastic responses of floating structures are studied.